R/B Enteric Differential System for Identification of Enterobacteriaceae - Smith, P. B. (1971)
The R/B Enteric Differential System for identifying enteric bacteria has been evaluated with 451 “unknown” cultures from the stock culture collection of the Center for Disease Control. An average of 89.6% of these cultures were correctly identified by the R/B system, when used as recommended by the manufacturer but without the assistance of serology. This percentage ranged, however, from 47% for Klebsiella to 100% for Serratia and Providencia. Of 11 groups or genera of Enterobacteriaceae tested, only three (Enterobacter, Serratia, and Providencia) were identified with 95% or better accuracy. Four groups (Arizona, Citrobacter, Escherichia, and Salmonella) attained 90 to 95% accuracy of identification, and three groups (Edwardsiella, Proteus, and Shigella) scored between 85 and 90% accuracy. We recommend the R/B system as a screening device which is reasonably successful in grouping bacteria but not as a substitute for more exacting conventional procedures.